Characterisation of sodium acetate treatment on acacia pennata natural fibres - Jaya Sheeba, Kasirajan Rajam.; Priya, Retnam Krishna; Prakash Arunachalam, Krishna.; Avudaiappan, Siva; Maureira Carsalade, Nelson.; Roco Videla, Ángel Gerardo. (MDPI, 2023)
The present study concerns the physico-chemical, structural, mechanical and thermal characterization of Acacia pennata, a natural and almost inexpensive fibre, as a potential reinforcement in polymer composites. The effect of treating the fibre with sodium acetate to increase its qualities has been seen through the use of thermogravimetric analysis, scanning electron microscope (SEM) analysis, X-ray diffraction (XRD), mechanical property tester, and Fourier transform infrared spectroscopy (FTIR). According to XRD analysis, the elimination of lignin and wax-like impurities resulted in an increase in the AP fibre’s crystalline index (79.73%). The fibre’s thermal stability was also discovered to be 365 °C. Tensile strength (557.58 MPa) and elongation at break both increased by 2.9% after treatment with sodium acetate. The surface nature and quality of AP fibres improved after sodium acetate treatment. It was confirmed by the reduction of chemical compositions (such as hemicellulose, lignin and pectin). Given its density, the fibre can be suggested as a reinforcement in polymer composites for light-weight applications because its lightweight property will be more useful for composite manufacturing.
Keywords: Chemical composition; Tensile strength; Thermal stability; X-ray diffraction; Espectroscopía infrarroja de transformación